Unveiling Drought-Resilient Latin American Popcorn Lines through Agronomic and Physiological Evaluation - Uéliton Alves de Oliveira; Antônio Teixeira do Amaral Junior; Jhean Torres Leite; Samuel Henrique Kamphorst; Valter Jário de Lima; Rosimeire Barboza Bispo; Rodrigo Moreira Ribeiro; Flávia Nicácio Viana; Danielle Leal Lamego; Carolina Macedo Carvalho; Bruna Rohem Simão; Talles de Oliveira Santos; et al. (Life, 2024)
Water stress can lead to physiological and morphological damage, affecting the growth and development of popcorn. The objective of this study was to identify the yield potential of 43 popcorn lines derived from a Latin American germplasm collection, based on agronomic and physiological traits, under full irrigation (WW) and water deficit conditions (WS), aiming to select superior germplasm. The evaluated agronomic traits included the ear length and diameter, number of grains per row (NGR) and rows per ear (NRE), grain yield (GY), popping expansion (EC), volume of expanded popcorn per hectare (VP), grain length (GL), width, and thickness. The physiological traits included the chlorophyll, anthocyanin, and flavonoid content in the leaves. The genetic variability and distinct behavior among the lines for all the agronomic traits under WW and WS conditions were observed. When comparing the water conditions, line L292 had the highest mean for the GY, and line L688 had the highest mean for the EC, highlighting them as the most drought-tolerant lines. A water deficit reduced the leaf greenness but increased the anthocyanin content as an adaptive response. The GY trait showed positive correlations with the VP, NGR, and GL under both water conditions, making the latter useful for indirect selection and thus of great interest for plant breeding targeting the simultaneous improvement of these traits.